2018
DOI: 10.1007/s12217-018-9636-3
|View full text |Cite
|
Sign up to set email alerts
|

Flow Patterns and Heat Transfer in a Cylindrical Annulus under 1g and low-g Conditions: Theory and Simulation

Abstract: A dielectric fluid is confined in a stationary vertical cylindrical annulus. A temperature difference is applied between the two cylinders, as well as an alternating electric potential. This configuration creates an active force called dielectrophoretic force, which acts as a thermal buoyancy force. Different axial gravity intensities are considered, so that two thermal buoyancies will affect the flow: the thermoelectric buoyancy intervenes in the radial direction and the Archimedean buoyancy acts in the axial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Meyer et al (2017) reported the flow after the first transition is axially aligned and consists of stationary columnar modes. Meier et al (2018) demonstrated experimentally the existence of those columnar modes for a few tuple of (∆T, V 0 ).…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Meyer et al (2017) reported the flow after the first transition is axially aligned and consists of stationary columnar modes. Meier et al (2018) demonstrated experimentally the existence of those columnar modes for a few tuple of (∆T, V 0 ).…”
Section: Introductionmentioning
confidence: 85%
“…Visualisation of the flow of cell with aspect ratio Γ = 20 is realised with the shadowgraph method (Merzkirch, 1987;Schöpf et al, 1996;Meyer et al, 2017;Meyer, 2017;Meier et al, 2018). Shadowgraph is a very simple technique and provides flow visualisation of very high quality.…”
Section: Shadowgraph Methodsmentioning
confidence: 99%
See 3 more Smart Citations